2018
DOI: 10.1021/acsami.8b08079
|View full text |Cite
|
Sign up to set email alerts
|

Locally Controlled Cu-Ion Transport in Layered Ferroelectric CuInP2S6

Abstract: Metal thiophosphates are attracting growing attention in the context of quasi-two-dimensional van der Waals functional materials. Alkali thiophosphates are investigated as ion conductors for solid electrolytes, and transition-metal thiophosphates are explored as a new class of ferroelectric materials. For the latter, a representative copper indium thiophosphate is ferrielectric at room temperature and, despite low polarization, exhibits giant negative electrostrictive coefficients. Here, we reveal that ionic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 44 publications
5
70
0
Order By: Relevance
“…The four possible polarization states in CIPS, ±LP and ±HP, are indicated. The energy barrier for Cu ions to cross the vdW gap is calculated to be ≈0.6 eV, which fits well in the range of reported activation barriers for Cu-ion conduction [32,35] and can be easily overcome using electric fields. If the Cu ions move beyond the unit cell and across the vdW gap along the z axis under the influence of an electric field, the resulting polarization exhibits unusual behavior.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The four possible polarization states in CIPS, ±LP and ±HP, are indicated. The energy barrier for Cu ions to cross the vdW gap is calculated to be ≈0.6 eV, which fits well in the range of reported activation barriers for Cu-ion conduction [32,35] and can be easily overcome using electric fields. If the Cu ions move beyond the unit cell and across the vdW gap along the z axis under the influence of an electric field, the resulting polarization exhibits unusual behavior.…”
Section: Resultssupporting
confidence: 79%
“…[28] In addition, CIPS has a high Cu-ion conductivity that extends into the temperature range of the ferroelectric phase. [30][31][32] It has been shown that in-plane ionic currents can be used to manipulate ferroelectric polarization. [33] These highly unusual properties that are rooted in the vdW structure provide the opportunity for complex polarization switching which might be exploited in transient-NC devices beyond the mechanisms discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Balke et al studied ionic conduction in CuInP 2 S 6 through local volume changes with the function of temperature and frequency. [96] The displacement induced by the driving field increases with an increasing temperature and drops with an increasing frequency, largely indicating that the ordering of the Cu ions in two off-center sites in the crystal lattice is the most possible explanation for CuInP 2 S 6 ferroelectricity. Although a systematic comparison measurement has been made in this article, the larger electromechanical response and higher contact resonance frequency contribute to a change in the topography, making the experimental results more complex to explain.…”
Section: Copper Indium Thiophosphatementioning
confidence: 99%
“…In contrast, the original downward polarization states remained unchanged. It has been reported that large crystallites can be formed at surface of CIPS when electrically switching ferroelectric domains 32,33 . In this work, we noted that no external electric eld was applied and no surface deformations were observed (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These unique characteristics not only bring new insights into the fundamental research 28,29 , but also provide new opportunities for diverse applications of layered ferroelectrics 30,31 . However, when electrically switching ferroelectric domains, the polar structure and ferroelectricity of CIPS can be readily damaged 32,33 due to its high ionic conductivity 34,35 . Because the ionic conductivity and polarization switching have common atomic origin-Cu atoms, it seems di cult to achieve a balance between these two processes.…”
Section: Introductionmentioning
confidence: 99%